Unsteady two-layered fluid flow of conducting fluids in a channel between parallel porous plates under transverse magnetic field in a rotating system - Linga Raju, Temburu; Neela Rao, B. (Zielona Góra: Uniwersytet Zielonogórski)
An unsteady MHD two-layered fluid flow of electrically conducting fluids in a horizontal channel bounded by two parallel porous plates under the influence of a transversely applied uniform strong magnetic field in a rotating system is analyzed. The flow is driven by a common constant pressure gradient in a channel bounded by two parallel porous plates, one being stationary and the other oscillatory. The two fluids are assumed to be incompressible, electrically conducting with different viscosities and electrical conductivities.
Keywords: magnetohydrodynamics; two-layered fluids/immiscible fluids; rotating fluids; oscillating flow; unsteady flow; porous plates